تحليل الأعراف الغير المشروعة في الأسرة الأفغانية في ضوء الفقه الإسلامي والقانون الأفغاني: An Analytical Study of Illegitimate Customary practices in Afghan Families in Light of Islamic Jurisprudence and Afghan Law - Naeem Hakimi, Mohammad; R.M. Elshobake, Mohammad; Bin Jaapar, Ghazali (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
ملخص البحث يتناول هذا البحث موضوع تحليل الأعراف الغير المشروعة في الأسرة الأفغانية في ضوء الفقه الإسلامي والقانون الأفغاني. وتكمن إشكالية البحث في وجود تباين بين الأحكام الشرعية والقانونية والعرفية السائدة في المجتمع الأفغاني. يهدف البحث إلى توضيح مفهوم الأعراف غير المشروعة، وبيان أحكامها، وتحليل موقف القانون الأفغاني منها، إضافة إلى استعراض تجلياتها التطبيقية في المجتمع، مع توضيح مفهوم الأسرة ودورها. يعتمد البحث على المنهج الاستقرائي، والمنهج التحليلي، والمنهج المقارن ومنج الملاحظة، والمقابلة في استقراء النصوص الشرعية، وتحليلها من الناحية القانونية، ومقارنتها بالواقع العرفي في أفغانستان. وتوصل البحث إلى أن الفقه الإسلامي قد وضع معالجات واضحة ومنضبطة للأعراف غير المشروعة، بينما نجد أن القانون الأفغاني يتأثر بشكل ملموس بالفقه الحنفي والتقاليد القبلية. ويوصي البحث بأهمية مراجعة وتحديث الأحكام الشرعية والقوانين المعمول بها، والعمل على تعزيز الوعي الأسري لضمان التوافق مع الشريعة الإسلامية ومقتضيات الحياة المعاصرة. ABSTRACT This study addresses the issue of illegitimate customs within the Afghan family in light of Islamic jurisprudence (Fiqh) and Afghan law. The research problem lies in the discrepancy between Sharia and legal provisions and the prevailing customary practices in Afghan society. The research aims to clarify the concept of illegitimate customs, explain their rulings, and analyze the stance of Afghan law towards them. Additionally, it seeks to review their practical manifestations in society, while also clarifying the concept of the family and its role. The study employs multiple research methodologies, including the inductive method, analytical method, and comparative method, as well as observation and interview method. These approaches are used to examine relevant Islamic legal texts, analyze them from a legal perspective, and compare them with the customary practices in Afghanistan. The research concludes that Islamic jurisprudence has established clear and regulated treatments for illegitimate customs, while Afghan law is found to be tangibly influenced by Hanafi jurisprudence and tribal traditions. The research recommends the importance of reviewing and updating the applicable Sharia rulings and laws, and working to enhance family awareness to ensure compatibility with Islamic Sharia and the requirements of contemporary life.